PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA UMKM FOTO COPY DI DUSUN VI KELAHANG DESA LABUHAN MARINGGAI LAMPUNG TIMUR - Dewi Hastina Dewi (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
This research aims to determine the effect of price and service quality on consumer satisfaction in photocopier MSMEs in VI Kelahang Village, Labuhan Maringgai District. Using a quantitative correlational research approach with a non-experimental type that uses ex post facto. This research sample used a random sampling method and obtained a total of 228 consumers from photocopying MSMEs in VI Kelahang Hamlet, Labuhan Maringgai District. The data analysis techniques used are the Classic Assumption Test, (Normality Test, Linearity Test, Multicollinearity Test, and Heteroscedasticity Test), Multiple Linear Regression Analysis, Hypothesis Test (t Test and F Test), and Coefficient of Determination. The research results ashow that partially there is a positive and significant influence between price and service quality on consumer satisfaction, while simultaneously there is an influence of price and service quality on consumer satisfaction.